Pengaruh Pendekatan Open Ended Berbasis Permainan Tradisional Terhadap Kemampuan Berfikir Kreatif Matematika Peserta Didik Kelas III SD - Silfiya, Nimas Santi; Hetilaniar, Hetilaniar; Nurhasana, Putri Dewi (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of an open ended approach based on traditional games that is effective on the creative thinking skills of students in grade III SD Negeri 11 Palembang. This research is a quasiexperimental type of research with a Nonequavalent control group design. The population in this study were allstudents of class III A and III B SD Negeri 11 Palembang, totaling 56 students. The sample in this study used a total sampling technique, namely a sampling technique where all members of the population were all sampled. The sample in this study was divided into two groups, namely the experimental group and the control groupwhere the experimental group consisted of 28 students and the control group consisted of 28 students. The instruments used in this study were tests, observations and documentation. The data analysis technique in this study used the independent sample t-test. The significance level in this study was 0.05 or the 95% confidencelevel. The experimental class that was given treatment with an open ended approach based on traditional games obtained a prettest-posttest average. The number of prettests is 54.6428 and the number of posttests is 84.6428 with an average prettest experimental class of 1,530 and a posttest of 2.370 and a control class prettest and posttest. The prettest was 56.4285 and the post-test was 75.35714, the average pre-test was 1.580and the post-test in the control class was 2.110. The results of the T-test with ttable 1.672 obtained tcount 4,320 it can be concluded that tcount > ttable which means that there is a significant influence on the use of an open ended approach based on traditional games on the mathematical creative thinking skills of third grade studentsof SD Negeri 11 Palembang.